Видове різноманіття та естетична характеристика насаджень селищного парку (смт Ілларіонове) - Іванченко, Ольга Євгенівна; Ivanchenko, Olga; Бессонова, Валентина Петрівна; Bessonova, Valentina (Дніпровський національний університет імені Олеся Гончара, 2020)
Проведено аналіз дендрофлори паркових насаджень смт Іларіонове. Установлено, що на території парку зростає 438 екз. дерев, які відносяться до 32 видів із 16 родин. Найчисельнішою деревною породою є Robinia pseudoacacia, у значній кількості представлені Acer platanoides та Acer negundo. Індекс видового різноманіття дорівнює 11,74. З наявного асортименту дерев 52,25 % мають декоративні квітки та суцвіття. 28,35 % усіх екземплярів деревної рослинності є аборигенними (12 видів). Середній діаметр штамбу дерев у насадженні парку складає 27 см, середня висота – 9,4 м. За фітосанітарним станом майже половина дерев без ознак ослаблення, з помірними пошкодженнями – 35,39 % усіх дерев. Індекс життєвого стану деревостану – 80,72. Спостерігається відповідність асортименту парку родючості ґрунту і лише часткова відповідність щодо режиму зволоження ділянки. Фітоценоз парку відноситься до ІІ класу естетичної цінності. Dendroflora of the park of the urban-type settlement Ilarionove consists of 438 exemplars of trees, mainly deciduous, which belong to 32 species. The most abundant species is Robinia pseudoacacia, the representativity of which is 25% in relation to the total number of trees in the garden and park object. Acer platanoides and Acer negundo (11.19 and 10.05%) are represented in significant quantities and Aesculus hippocastunum is represented in sufficient quantities. The families are represented mainly by 1–2 species, with the exception of Aceraceae, Salicaceae and Ulmaceae, which included 4, 4, and 3 species, respectively. The decorative trees that are blooming amount to 52,25 % of all plants in the park. The biodiversity index is 11,74, which is quite high compared to other parks in the Dnipropetrovsk region. 71.65% of all trees in the park are introduced species, whose homeland is mainly North America. Trees in the park grow mainly in rows (Acer platanoides, Aesculus hippocastunum and Gleditschia triacanthos) and some in groups as hedgerows (Spiraea vanhouttei). As to the stem diameter, the most numerous are groups with relevant indicator value of 14,1–18,0; 32,1– 38,0 and 38,1–42,0 – 12,56; 12,32 and 12,32 % relative to the number of all trees in the park. The average trunk diameter is 27 cm. The height of about half of the trees ranges from 8,1 to 12,0 m – 52.09 % of the total number of exemplars. As for the vitality, 51,37 % of park trees are without signs of damage, moderately weakened trees amount to 35,39%, no dead-standing trees have been detected. According to the requirements for productive capacity of soil, the available assortment of woody plants in the park corresponds to the soil conditions of the territory, but only partially to the moisture regime. In terms of aesthetic value, the phytocenosis of the park is classified as class II
Species diversity and aesthetic characteristics of the planting of the settlement park (urban-type settlement Ilarionove)
Keywords: парк смт Іларіонове; Illarionovo town park; зелені насадження; green plantings; дендрофлора; dendroflora; таксаційні характеристики; taxation characteristics; фітосанітарний стан; phytosanitary condition; фітоценоз; phytocenosis; естетична оцінка; aesthetic evaluation